Detection and characterization of zoonotic dermatophytes from dogs and cats in and around Kolkata - S. Murmu (Veterinary World, 2015)
Aim: The ringworms of pet dogs, cats, and stray animals (dogs, cats, and other animals) could be a potential source of zoonotic infections causing a serious public health problem in the busy city Kolkata. The pet owners are more susceptible to get this infection from their pets, because of the close contact with them as dermatophytosis is very much prevalent in those pets. So, this study was aimed to check the prevalence of dermatophytosis in dogs, cats, and in pet owners. Materials and Methods: A total of 362 clinically suspected cases of dermatophytosis from dogs (123 in number), cats (202 in number), and human beings (37 in number) were collected and studied from in and around Kolkata to detect the presence of significant dermatophytes. Direct microscopy and cultural examination of the isolates were performed following standard methodology. Identification and characterization of the isolates were done by different biochemical tests. Results: Samples (n=285) having significant dermatophytic fungal infections were found to be of highest number in cats (158, 55.5%) than in dogs (108, 37.8%) and humans (19, 6.7%), respectively. The incidence of Microsporum canis (60.0%) was the highest from affecting dogs, cats, and human beings in comparison to Microsporum gypseum (22.5%), Trichophyton mentagrophytes (15.8%) and Trichophyton rubrum (1.7%). Detection of T. rubrum was only from human cases in this study, whereas the presence of rest three were slightly higher in cats than that of the dogs and humans in this present study. The incidences were higher in young animals and in humans of the age group of 21-30 years, during the rainy season (from April to August) and also in in-contact human beings. Conclusion: M. canis was the most commonly pathogen among all causing dermatophytosis in animals and also in the pet owners. M. gypseum and T. mentagrophytes were other pathogens associated with these infections. These infections were more prevalent in the rainy seasons and in in-contact human patients or pet owners.